Chronic rhinosinusitis with nasal polyposis (CRSwNP): the correlation between expression of Galectin-10 and Clinical-Cytological Grading (CCG). Issue 2 (March 2022) - Gelardi, Matteo; Netti, Giuseppe Stefano; Giancaspro, Rossana; Spadaccino, Federica; Pennella, Antonio; Fiore, Valeria; La Gatta, Emanuel; Grilli, Gianluigi Mariano; Cassano, Michele; Ranieri, Elena
Background: Chronic rhinosinusitis with nasal polyps (CRSwNP) is typically characterized by Type 2 inflammation. Several biomarkers of eosinophilic inflammation, including Galectin-10, also known as Charcot-Leyden crystal protein (CLCP), have been identified to establish eosinophilic infiltration of polyps, a reliable predictor of recurrence. Objective: We aimed to evaluate the Galectin-10 expression in nasal polyps of patients with CRSwNP and to assess the correlation of Charcot-Leyden crystals expression to the severity of CRSwNP according to Clinical-Cytological Grading (CCG). Methods: A double-label immunofluorescence was performed to evaluate the expression of Gal-10, CD15, Tryptase, and CD63 and their eventual co-localization on histological samples of 18 patients with CRSwNP. Double-positive Gal-10+CD15+ and Galectin-10+Tryptase+ inflammatory cells were counted by confocal microscopy. Results: Galectin-10 was detectable in all examined tissues from CRSwNP patients, and its expression increased as low, medium and high CCG tissues were examined, respectively. Galectin-10 was extensively present in inflammatory cells, while limited Galectin-10 deposits were detected around mucosal epithelial cells. Conclusion: We showed the strong correlation between CCG and Galectin-10 expression, mainly colocalized with infiltrating eosinophils and mast-cells, in patients affected by CRSwNP.